Rammed earth wall’s thermal behaviour carachterization by termofluxometry - CASTELLARNAU VISÚS, ÀNGELS (Restauro Compás y Canto S.A., 2020)
The large amount of Spanish earth built heritage that already requires urgent rehabilitation, the emergence of new sustainability criteria that pushes up contemporary earth architecture and the need of compliance with the standard for the reintroduction in the Spanish construction system of the earth building techniques, oblies to review the data and the methodology for the parameterization of the earth wall’s thermal behaviour. It’s necessary the homologation of the earthen buildings to the current building regulations and the formulation of new protocols adapted to the peculiarity of their dynamic behaviour. The lack of research related to quantification of the thermal behaviour of this type of building solutions casts doubts about their conformability. The objective of the present research is to characterize the thermal behaviour of a north rammed earth façade of a contemporary building taking into account both the heat flow ​​from the inside ambient towards the inside of the wall and the heat flow from the wall towards the outside ambient. Methodology is based on monitoring the ambient surface temperatures and the heat flow under certain conditions (in compliance with the standardized in situ monitoring tests of the thermal behaviour of building envelopes) to obtain the U values​​. It is characterized the dynamic behaviour of the wall. The results characterize the dynamic behaviour of the wall, reveal its positive vulnerability to the outside temperature and determine the inefficiency of the regulation’s methodology in case of walls with thermal inertia. Despite this, the data obtained improves significantly the values ​​that are reflected in the current Spanish building regulations and those that appear in reference bibliographies.